2012
DOI: 10.1242/dev.075572
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of pectoral fin outgrowth in zebrafish development

Tohru Yano,
Gembu Abe,
Hitoshi Yokoyama
et al.

Abstract: . (2010). Loss of fish actinotrichia proteins and the fin-to-limb transition. Nature 466, 234-237.We apologise to the authors and readers for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 62 publications
1
66
0
Order By: Relevance
“…Each fin/limb bud possesses an apical ectodermal ridge (AER) and zone of polarizing activity (ZPA) [40], [41], which play important roles in growth and patterning [42]–[44]. The AER, a thickened epithelium that rims the distal ends of the buds, is the source of Fgf signals required for P-D limb outgrowth [45][48]. The zebrafish AER expresses 4 fgf genes: fgf4 , fgf8a , fgf16 and fgf24 [49], [50].…”
Section: Resultsmentioning
confidence: 99%
“…Each fin/limb bud possesses an apical ectodermal ridge (AER) and zone of polarizing activity (ZPA) [40], [41], which play important roles in growth and patterning [42]–[44]. The AER, a thickened epithelium that rims the distal ends of the buds, is the source of Fgf signals required for P-D limb outgrowth [45][48]. The zebrafish AER expresses 4 fgf genes: fgf4 , fgf8a , fgf16 and fgf24 [49], [50].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the AER in tetrapods, which is maintained during limb bud outgrowth, the AER in fish fin buds differentiates into an extended structure, the apical ectoderm fold (AEF), which lifts off the mesenchyme at an early stage and elongates to give rise to the dermoskeleton (Thorogood, 1991). Studies have shown that the repeated experimental removal of the AEF from zebrafish fin buds results in increased mesenchymal cell proliferation and excessive elongation of the mesenchyme, suggesting that prolonged exposure to AER signals induces distal elongation of mesenchyme and the endoskeleton (Yano et al, 2012). By contrast, overexpression of the distal hoxd13a gene in fin buds reduces the size of the AEF and distal expansion of chondrogenic tissue (Freitas et al, 2012).…”
Section: Molecular Insights Into the Fin-to-limb Transitionmentioning
confidence: 99%
“…Particularly, the tetrapod Dlx5 / Dlx6 and teleost dlx5a/dlx6a genes are expressed in the apical ectodermal ridge (AER) of the developing limbs in mice [12][15] and in the pectoral fin fold (PFF) and median fin fold (MFF) giving rise respectively to paired and unpaired fins in zebrafish [16][19]. At early stage of fin morphogenesis, teleosts present an AER structurally homologous to the AER of tetrapods [1], [20]. Later, the AER transitions into an elongated pectoral fin fold [20].…”
Section: Introductionmentioning
confidence: 99%
“…At early stage of fin morphogenesis, teleosts present an AER structurally homologous to the AER of tetrapods [1], [20]. Later, the AER transitions into an elongated pectoral fin fold [20]. AER and fin fold structures have been demonstrated to be essential signaling centers during appendage specification and outgrowth in vertebrates [7], [17], [20][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation